Analyses of LTR-Retrotransposon Structures Reveal Recent and Rapid Genomic DNA Loss in Rice - Ma, Jianxin; Devos, Katrien M.; Bennetzen, Jeffrey L. (Genome Research, 2004)
We initially analyzed 11 families of low- and middle-copy-number long terminal repeat (LTR) retrotransposons in rice to determine how their structures have diverged from their predicted ancestral forms. These elements, many highly fragmented, were identified on the basis of sequence homology and structural characteristics. The 11 families, totaling 1000 elements, have copy numbers ranging from 1 to 278. Less than one-quarter of these elements are intact, whereas the remaining are solo LTRs and variously truncated fragments. We also analyzed two highly repetitive families (Osr8 and Osr30) of LTR retrotransposons and observed the same results. Our data indicate that unequal homologous recombination and illegitimate recombination are primarily responsible for LTR-retrotransposon removal. Further analysis suggests that most of the detectable LTR retrotransposons in rice inserted less than 8 million years ago, and have now lost over two-thirds of their encoded sequences. Hence, we predict that the half-life of LTR-retrotransposon sequences in rice is less than 6 million years. Moreover, our data demonstrate that at least 22% (97 Mb) of the current rice genome is comprised of LTR-retrotransposon sequences, and that more than 190 Mb of LTR-retrotransposon sequences have been deleted from the rice genome in the last 8 million years.